Faktor yang Memengaruhi Kejadian Diare pada Balita di Wilayah Puskesmas Tanjung Sekayam Kabupaten Sanggau Kalimantan Barat - Bustamil Arifin; Ismail Efendy; Ramadhani Syafitri (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Toddler age is a period of rapid growth and development, a state that is vulnerable to nutrition and susceptible to disease. Diarrhea in toddlers if not treated seriously can cause pain, to severe dehydration or fluid loss that ends in death. The current diarrhea control program is more prioritized on diarrhea control programs for toddlers. This research method is cross-sectional with a population of mothers and toddlers with a sample size of 175 respondents. The results of this study showed the influence of the mother's education level (p-value 0.011), exclusive breastfeeding (0.003), socio-economic (0.008), hand washing habits (0.007) on the incidence of diarrhea in toddlers in the Tanjung Sekayam Health Center Area, Sanggau Regency. The conclusion of this study is that there is an influence of the mother's education level, exclusive breastfeeding, socio-economic, hand washing habits on the incidence of diarrhea. It is expected that health workers will carry out health promotion activities about the incidence of diarrhea in toddlers to prevent infectious diseases that will result in stunting.